2002
DOI: 10.1177/03635465020300021201
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Comparison of Patellar Tendon versus Semitendinosus and Gracilis Tendon Autografts for Anterior Cruciate Ligament Reconstruction

Abstract: Seventy patients with patellar tendon or hamstring tendon autografts for single-incision anterior cruciate ligament reconstruction were evaluated at least 2 years after surgery. All reconstructions were performed by the same surgeon, and metal interference screws were used for fixation of all grafts. No significant differences were noted between groups for Lysholm score, reduction in activity, KT-1000 arthrometer findings, quadriceps muscle size, return to sports, or ability to jump and do hard cuts and pivots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
254
5
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(287 citation statements)
references
References 30 publications
14
254
5
14
Order By: Relevance
“…In the paper by Biau and co-workers, we identified 14 primary studies with data available on anterior knee pain from 1991 to 2005 (Marder et al 1991, Aglietti et al 1994, 1997, Callaway et al 1994, Aune et al 2001, Eriksson et al 2001a, b, Feller et al 2001, Ropke et al 2001, Beynnon et al 2002, Shaieb et al 2002, Ejerhed et al 2003, Feller and Webster 2003, Hantes et al 2004, Ibrahim et al 2005, Laxdal et al 2005, Biau et al 2006). Our cumulative meta-analysis showed that statistical significance that hamstring autograft reduces ante- …”
Section: Cumulative Meta-analysis On Anterior Knee Pain (Figure 1)mentioning
confidence: 99%
“…In the paper by Biau and co-workers, we identified 14 primary studies with data available on anterior knee pain from 1991 to 2005 (Marder et al 1991, Aglietti et al 1994, 1997, Callaway et al 1994, Aune et al 2001, Eriksson et al 2001a, b, Feller et al 2001, Ropke et al 2001, Beynnon et al 2002, Shaieb et al 2002, Ejerhed et al 2003, Feller and Webster 2003, Hantes et al 2004, Ibrahim et al 2005, Laxdal et al 2005, Biau et al 2006). Our cumulative meta-analysis showed that statistical significance that hamstring autograft reduces ante- …”
Section: Cumulative Meta-analysis On Anterior Knee Pain (Figure 1)mentioning
confidence: 99%
“…Many conflicting publications exist with no real consensus. Improved long-term stability in the patellar tendon group and decreased sensory deficits in the hamstrings group are some of the tendencies shown in these studies [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized, controlled trials have previously demonstrated the superiority of reconstruction compared with primary repair [1][2][3] . Additional randomized, controlled trials have shown no clinical differences in outcome between the use of patellar tendon autograft and the use of hamstring tendon graft [4][5][6][7][8][9][10][11] or between one and two-incision arthroscopic operative techniques 10,[12][13][14] . Thus, reconstructions of the anterior cruciate ligament have been performed to allow patients to resume activities, especially in sports requiring cutting and pivoting, and studies have shown overall good short-term function 15,16 .…”
mentioning
confidence: 99%